KERAGAAN AGROINDUSTRI MAKANAN DI DESA MOJOPAHIT KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Aryogi, Riski Tri; Indriani, Yaktiworo; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This study aims to analyze the performance of food agro-industry.  This research was employed  case study method at D’Lia Foods at Mojopahit Village in Punggur District of Central Lampung Regency. The respondents  were involved the owner and two employees of the agroindustry,  and seven retailers  for the marketing channel. . Data collection was carried out from December 2023 to January 2024, and analyzed by descriptive qualitatively and quantitatively. The results show  that the supply chain flow pattern of product raw materials at D'Lia Foods Agroindustry comes from several districts with some predetermined criterias, and  the  financial flow between suppliers/producers and agro-industry required cash money. The information flows in two directions related to ordering raw material stocks. The labor productivity of dodol pineapple is 0.85 kg/hour, pineapple salad is 0,50 kg/hour, shredded pineapple skin is 0,67 kg/hour, and tiwul chips is 1,07  kg per hour. .  The profit from each product  is IDR 4,073,843.24 per production. The study indicates two marketing channels of the products , namely level I channels, and level II channels. The role of supporting services is the most utilized in the marketing section and has a positive impact on the activities of D'Lia Foods Agroindustry. Keywords: agroindustry, performance, pineapple, processed, tiwul